2018
DOI: 10.1051/matecconf/201824803002
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Selection to the Awareness of Energy-Saving Behavior in the Public Sector

Abstract: Nowadays Indonesia is facing energy scarcity and still struggling with finding new energy resources. No other ways the employee have to use the currently available energy wisely. However wasteful behavior in energy use is still often seen in public sectors like government/private buildings, schools/campuses, hospital, and others. Various effort (such as energy saving campaign through mass media, pamphlet, etc) have been made by the building managers or owners to encourage users energy-saving behavior through v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, the authors found that other noneconomic factors may play a role in the adjustment of electricity efficiency behaviors. Linda et al (2018) found that interventions for building awareness of energy conservation behavior are mostly conducted through directive appeals from figures of authority combined with monetary incentives, whereas consequences are regulated by controlling government policy and regulations. Nevertheless, this stick-and-carrot approach failed to produce the optimal level of awareness and actions among the public.…”
Section: Psychological Research On Urban Societymentioning
confidence: 99%
“…However, the authors found that other noneconomic factors may play a role in the adjustment of electricity efficiency behaviors. Linda et al (2018) found that interventions for building awareness of energy conservation behavior are mostly conducted through directive appeals from figures of authority combined with monetary incentives, whereas consequences are regulated by controlling government policy and regulations. Nevertheless, this stick-and-carrot approach failed to produce the optimal level of awareness and actions among the public.…”
Section: Psychological Research On Urban Societymentioning
confidence: 99%
“…Electricity is an important form of energy. It is a fundamental indicator for many aspects like economic development, uses of technology tools, employment, and economic competitiveness [1][2][3]. According to the central statistics agency, with the rapid increase in a short period of electricity use, there might be a global scarcity of electrical energy [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the negligence of electricity meter users in managing the use of electrical energy that is spent every day can also affect the increase in electrical energy. Several factors influence the increase in electrical energy, namely human factors (80%) and other technical factors (20%) [1]. Quoted from the official website of the Central Statistics Agency (BPS), it is known that electricity consumption in 2017 rose by around 1.02 mWh/capita, then in 2018, it rose by around 1.06 mWh/capita, and in 2019 it rose again to reach 1.08 mWh/capita [2].…”
Section: Introductionmentioning
confidence: 99%